ISLAMIC LAW REVIEW OF THE VALIDITY OF SELF-DECLARATION IN THE HALAL CERTIFICATION PROCESS OF MICRO AND SMALL BUSINESSES (MSEs) - Apra Muthiah Azizah Amatullah; Hadi Daeng Mapuna; Suriyadi (El-Iqthisadi, 2025)
Abstract This research is entitled Islamic Law Review of the Validity of Self declare in the halal certification process of micro and small businesses (MSEs). The main problem of this research is How is the Islamic Law Review of the validity of self-declaration in the halal certification process of micro and small businesses (MSEs)? From this main problem, sub- problems can be formulated, namely (1) What is the concept of self-declaration in halal certification in Indonesia? (2) How are the provisions of Islamic law regarding certification given on the statement of business actors? The objectives of this study are (1) to find out how the concept of self-declaration in halal certification in Indonesia, (2) to find out how the provisions of Islamic law on certification are given on the statement of business actors. The type of research used is library research or library research. The method used is data collection which is done by reading references and literature with the aim of supporting this research. The research approach used is the Shari'i Theological Approach with a normative juridical approach. The results of the study indicate that halal certification with a self- declaration scheme in the perspective of Islamic law is said to be valid, because the concept of self-declaration in Indonesia does not necessarily mean that business actors can declare that their products are halal, but there are still mechanisms that regulate the self-declaration such as products that are not risky or use materials that have been confirmed halal and PPH assistance is carried out. In addition, the presence of self-declaration has fulfilled the three basic principles of muamalah fiqh, namely the Principle of Tawhid, the Principle of Mubah, the Principle of Maslahah. The implication of this research is to help ensure that products claimed to be halal by micro and small businesses (MSEs) through the self-declaration scheme actually meet halal standards recognized by Islamic law, so that consumers can have greater confidence in the products in circulation, besides that this research is also expected to be the basis for improving regulations related to halal certification of self-declaration schemes, including improving supervision and monitoring mechanisms to prevent unauthorized self-declaration practices. Keywords: Validity, Halal Certification, Self declare